2010
DOI: 10.1111/j.1471-0528.2010.02596.x
|View full text |Cite
|
Sign up to set email alerts
|

Low–moderate prenatal alcohol exposure and risk to child behavioural development: a prospective cohort study

Abstract: Objective To examine the association of fetal alcohol exposure during pregnancy with child and adolescent behavioural development.Design The Western Australian Pregnancy Cohort (Raine) Study recruited 2900 pregnancies and the 14-year follow up was conducted between 2003 and 2006.Setting Tertiary obstetric hospital in Perth, Western Australia.Population The women in the study provided data at 18 and 34 weeks of gestation on weekly alcohol intake: no drinking, occasional drinking (up to one standard drink per w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
3
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 40 publications
10
111
3
6
Order By: Relevance
“…In the UK (Millennium Cohort Study) Kelly et al 138 suggest there is no increased risk of behavioural or cognitive deficits at the age of 3 years for children whose mothers drank within recommended limits compared with children whose mothers did not drink. Indeed, boys born to light-drinking mothers were less likely to have conduct/hyperactivity problems, showing some apparently protective effects of alcohol, with similar findings in Australia, 139 although there may be important confounding factors as light alcohol consumption is noted as a marker of relative socioeconomic advantage, which can influence children's social and emotional behaviours. These effects were shown to continue until children reached 5 years of age.…”
Section: Effects Of Light To Moderate Drinking In Pregnancymentioning
confidence: 55%
See 1 more Smart Citation
“…In the UK (Millennium Cohort Study) Kelly et al 138 suggest there is no increased risk of behavioural or cognitive deficits at the age of 3 years for children whose mothers drank within recommended limits compared with children whose mothers did not drink. Indeed, boys born to light-drinking mothers were less likely to have conduct/hyperactivity problems, showing some apparently protective effects of alcohol, with similar findings in Australia, 139 although there may be important confounding factors as light alcohol consumption is noted as a marker of relative socioeconomic advantage, which can influence children's social and emotional behaviours. These effects were shown to continue until children reached 5 years of age.…”
Section: Effects Of Light To Moderate Drinking In Pregnancymentioning
confidence: 55%
“…139 This makes alcohol more 'complex' than tobacco, for example, in terms of public health messages, as there is clear unambiguous evidence that all smoking is bad. This lack of clear evidence about alcohol consumption in pregnancy led some participants to express concerns about the possibilities of developing consistent messages for women, as 'getting people to make behaviour changes relies on clear, simple information about what to do' (Public Health 37).…”
Section: Public Health 37mentioning
confidence: 99%
“…After screening and review, 23 articles were included in qualitative or quantitative analysis, with between 2 and 8 articles (total: 16) included in various meta-analyses. Tables 3 and 4 show the characteristics of included studies, according to presence of FASD (10 studies) [13][14][15][16][17][18][19][20][21] or PAE (14 studies), respectively [22][23][24][25][26][27][28][29][30][31][32][33][34] : one study reported data for both PAE and FASD. 35 Most were from North America (n = 15; 65.2%), followed by Australia (n = 4) and Canada (n = 2), with 1 study each from Finland and Taiwan.…”
Section: Literature Searchmentioning
confidence: 99%
“…Only 3 studies reported OR for our primary outcomes. 29,31,32 Exploratory forest plots were created, incorporating the 3 primary "problems" scores (Total, Externalizing, and Internalizing problems) to examine whether odds of having problematic behavior ratings were higher after PAE. These primary outcomes, grouped by standardized PAE categories based on O'Leary et al, 12 indicated no increased odds for poorer behavior ratings with higher PAE levels (data not shown).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation